Vegetation Regulates Element Composition of Soils by Enhancing Organic Matter Accumulation in the Salt Marshes of Liao River Delta, China - Wang, Guodong; Wang, Ming; Xue, Zhenshan; Ren, Zhibin; Jiang, Ming; Otte, Marinus (Frontiers in Marine Science, 2022)
The purpose of this study was to evaluate if vegetation regulates soil biogeochemistry in coastal salt marshes, here measured as element concentrations (43 elements) and organic matter content of the soils. We selected seven sampling sites in Liao River Delta, China, within each of which three areas existed in close proximity of each other, characterized as ‘bare, unvegetated sediments’, ‘Phragmites australis marsh’, and ‘Suaeda heteroptera marsh’. We recorded sampling locations and measured soil element concentrations, organic matter content, soil pH, soil salinity, soil water content, and soil electrical conductivity. All but four of element concentrations of soils varied by wetland type, and concentrations of 35 elements, and organic matter content increased from bare, unvegetated sites to Phragmites marshes to Suaeda marshes. Redundancy analysis (RDA) identified that organic matter content explained most variance. Organic matter content was positively related with most elements including nutrients and metals, negatively related with Sr, Ba and Na. However, further analysis of element concentrations revealed significant differences also between Phragmites-dominated and Suaeda-dominated sites, even though they did not differ significantly in organic matter content. This information highlights the importance of vegetation in regulating soil element composition and biogeochemical processes in coastal salt marshes.